Library service experience during and post COVID-19 outbreak: the case of the National Library of China - Yang, Li (Access: An International Journal of Nepal Library Association, 2022)
Faced with the threat of COVID-19 outbreak, public libraries developed innovative practices to deal with the pandemic by providing information service, expanding online and digital service and reading promotion activities. The aim of the study is to explore the service experience of the National Library of China during the outbreak and after the reopening. It is found that the enrichment of online and digital services, as well as the combination with the use of social media, facilitate the service provided during the closure and also bring new angels into the development of libraries in the post pandemic era.